2002
DOI: 10.1081/dmr-120005668
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF HUMAN CYTOCHROME P450 (CYP) IN THE METABOLIC ACTIVATION OF NITROSAMINE DERIVATIVES: APPLICATION OF GENETICALLY ENGINEEREDSALMONELLAEXPRESSING HUMAN CYP

Abstract: The role of human cytochrome P450 (CYP) in the metabolic activation of tobacco-related N-nitrosamines was examined by Salmonella mutation test using a series of genetically engineered Salmonella typhimurium YG7108 strains each co-expressing a form of CYP (CYP1A1, CYP1A2, CYP1B1, CYP2A6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, CYP3A4, and CYP3A5) together with human NADPH-cytochrome P450 reductase. Seven tobacco-related N-nitrosamines such as 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone, N-nitrosodiethylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Presence of the 96-bp insert in the CYP2E1 gene is known to be associated with increased enzyme activity [19]. The CYP2E1 enzyme is mainly involved in metabolic activation of N-nitrosamines (a well-defined factor for gastric carcinogenesis) [35]. Therefore, the CYP2E1 genotype frequency observed in the present study is in accordance with this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…Presence of the 96-bp insert in the CYP2E1 gene is known to be associated with increased enzyme activity [19]. The CYP2E1 enzyme is mainly involved in metabolic activation of N-nitrosamines (a well-defined factor for gastric carcinogenesis) [35]. Therefore, the CYP2E1 genotype frequency observed in the present study is in accordance with this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…Each CYP form shows some substrate specificity for activating promutagens to their mutagenic intermediates (Vermeulen, 1996). CYP2E1 is responsible for α-hydroxylation of N-alkylnitrosamines with a short alkyl chain (Bellec et al, 1996) whereas cyclic N-nitrosamines, such as NPIP and NPYR, are primarily activated by CYP2A6, and to lesser extent by CYP2E1 (Kamataki et al, 2002). Finally CYP1A1 is a molecular form of CYP playing a major role in the metabolic activation of NDBA (Fujita and Kamataki, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The result confirmed that CYP2E1 is the principal enzyme responsible for the metabolic activation of DMN in human liver microsomes as shown in the previous studies. [4][5][6][7][8] Nine halogenated anilines, 3,5-diF-A, 3,4,5-triF-A, 2,6-diCl-A, 3,4-diCl-A, 3,5-diCl-A, 2,3,4-triCl-A, 2,4,6-triCl-A, 3,4,5-triCl-A, and 2,6-diBr-A, were subjected to analysis of their inhibitory effects on metabolic activation of DMN in human liver microsome (HG56) to evaluate their CYP2E1/2A6-selective inhibition. The inhibitory activities (IC 50 ) of these anilines on human recombinant CYP2E1, CYP1A2, and CYP2A6 activities are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] It is well-known that CYP2E1 and CYP2A6 are responsible for activation of carcinogenic nitrosamines, and CYP2E1 may be the major enzymes catalyzing the metabolic N-demethylation of DMN in human liver microsomes. [4][5][6][7][8] Our previous study indicated that 3,4-dichloroaniline (3,4-diCl-A) and 3,5-diCl-A showed potent inhibition of recombinant human CYP2E1 (IC 50 = 8.0 and 9.2 µM, respectively) and no inhibition of CYP1A2 (IC 50 > 200 µM). 9) Moreover, the inhibitory effects of the anilines on CYP2E1 were widely affected by the substituted halogen species, number, and positions.…”
Section: Introductionmentioning
confidence: 99%